Preliminary estimates of the contribution of Arctic nitrogen fixation to the global nitrogen budget. Issue 5 (28th July 2017) - Sipler, Rachel E.; Gong, Donglai; Baer, Steven E.; Sanderson, Marta P.; Roberts, Quinn N.; Mulholland, Margaret R.; Bronk, Deborah A.
Abstract: Dinitrogen (N2 ) fixation is the source of all biologically available nitrogen on earth, and its presence or absence impacts net primary production and global biogeochemical cycles. Here, we report rates of 3.5–17.2 nmol N L −1 d −1 in the ice‐free coastal Alaskan Arctic to show that N2 fixation in the Arctic Ocean may be an important source of nitrogen to a seasonally nitrogen‐limited system. If widespread in surface waters over ice‐free shelves throughout the Arctic, N2 fixation could contribute up to 3.5 Tg N yr −1 to the Arctic nitrogen budget. At these rates, N2 fixation occurring in ice‐free summer waters would offset up to 27.1% of the Arctic denitrification deficit and contribute an additional 2.7% to N2 fixation globally, making it an important consideration in the current debate of whether nitrogen in the global ocean is in steady state. Additional investigations of high‐latitude marine diazotrophic physiology are required to refine these N2 fixation estimates.